Meat Handling and Safety Practices among Meat Handlers: A Cross-sectional Study in a Metropolitan City of Maharashtra - Davuluri, Praveen; Bisen, Pratima; Rawat, Shalini; Tiwari, Sayali (Journal of Public Health and Primary Care, 2025)
Abstract Background: Meat handling and safety practices are critical components of food safety, and they play a vital role in ensuring the safety and quality of meat products. This study was conducted to assess the meat handling practices among meat handlers in the field practice area of an urban health center. Methodology: This was a cross-sectional observational study done in the field practice area of an urban health training center of a medical college. The study was conducted for 2 years (January 2014-December 2015). The total sample was 185. A complete enumeration method was used in this study to include all the meat handlers working in the study area. All meat handlers who were working in this profession for a period of not <1 year and who were willing to participate were included in the study. Ethical approval was taken from the institutional ethics committee. Data entry was done by the investigator using Microsoft Excel 2007 version. Statistical analysis was done using SPSS version 21. Results: A majority (145; 84.8%) of meat handlers know how to differentiate between viable and nonviable meat, whereas only 26 (15.2%) of the subjects did not have this knowledge. One hundred and six (61.99%) reported that they regularly wash their hands before having food, as opposed to the 65 (38.01%) subjects who did not. Eighty-four (49.12%) of the study subjects cleaned their instruments ≤5 times a day, whereas 87 (50.88%) of them did it >5 times per day. The arbitrary scoring of personal hygiene among the study subjects reveals that a majority of study subjects, i.e., 113 (66.08%), showed a poor personal hygiene score. Conclusion: There was a lack of awareness among the meat handlers due to inadequate training on meat hygiene practices. Periodic training programs should be conducted to educate them. Washing hands before having food and after using the toilet should be encouraged.